Long-term immunogenicity of measles, mumps and rubella-containing vaccines in healthy young children: A 10-year follow-up. Issue 36 (23rd August 2019) - Carryn, Stephane; Feyssaguet, Muriel; Povey, Michael; Di Paolo, Emmanuel
Highlights: Measles-mumps-rubella (MMR)-containing vaccines provide robust immune responses up to 10 years. Antibody levels persisted above seropositivity threshold for all three antigens over 10 years. Anti-measles antibody titers elicited by Priorix-Tetra remain 2-fold higher than Priorix over 10 years. A second dose of a MMR-containing vaccine, whenever given, boosts anti-mumps antibody levels. Abstract: Measles and mumps outbreaks still occur in countries that have successfully implemented universal routine immunization programs. Measles outbreaks are mostly associated to absent or incomplete vaccination, whereas for mumps outbreaks the combined effects of waning of immunity and circulating new strains are incriminated. It is therefore increasingly useful to characterize the long-lasting immunity induced by measles-, mumps, and rubella (MMR)-containing vaccines. In this 10-year study, 1887 healthy children aged 12–22 months, randomized to receive 1 or 2 doses of MMR-containing vaccines ( Priorix or Priorix-Tetra ; GSK), were included in an antibody persistence analysis. A total of 364 children in the 1-dose group received a second dose out of study according to their local vaccination schedule between Years 4 and 10 post-dose 1, and were included in a separate post-hoc analysis to evaluate the effect of the second dose when given later. Anti-measles, -mumps and -rubella antibody titers were measured by commercial ELISA kits (Enzygnost, Siemens) after each vaccine dose and at Years 1, 2, 4, 6, 8 and 10 post-vaccination. Antibodies against measles and rubella declined moderately after vaccination but remained well above the seropositivity threshold after 10 years. The anti-measles antibody titers elicited by Priorix-Tetra remained about 2-fold higher throughout the study as compared with Priorix . A second dose of MMR vaccine later in life had a minor and transient effect on anti-measles and anti-rubella waning titers. In contrast, anti-mumps antibody levels remained relatively stable over the 10-year follow-up and a second dose of MMR vaccine, given anytime over the 10-year period, had a boosting effect on anti-mumps antibody titers and seropositivity rates. In conclusion, 1 or 2 doses of MMR-containing vaccines given to children in their second year of life induced antibody responses against measles, mumps and rubella viruses that persisted at least up to 10 years post-vaccination. Clinical trial registration number: NCT00226499.